2009
DOI: 10.3746/jkfn.2009.38.4.442
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in HT-29 Human Colon Cancer Cells by the Pepper Component Piperine

Abstract: Piperine is an alkaloid-amine found in pepper and has been reported to have anticarcinogenic properties. To explore the possibility that piperine has cancer chemopreventive and chemotherapeutic effects in colon cancer, we examined whether piperine inhibits the growth of HT-29 human colon cancer cells and investigated the mechanisms for this effect. Cells were cultured with various concentrations (0~40 μM) of piperine. Piperine decreased the cell viability and induced apoptosis of HT-29 cells. Western blot anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In a comparison with the control group, DAPI-positive cells increased by more than 3-fold depending on the concentration of piperine used. Shin et al reported the concentration-dependent increase in apoptotic bodies in AGS stomach cancer cells treated with piperine in (100 and 150 μM) (27), while Kim et al observed apoptotic bodies in HT-29 colon cancer cells treated with 40 μM piperine (28). These findings suggest that the decreases in the survival rates of A375SM and A375P treated with piperine were caused by apoptosis induction.…”
Section: Discussionmentioning
confidence: 98%
“…In a comparison with the control group, DAPI-positive cells increased by more than 3-fold depending on the concentration of piperine used. Shin et al reported the concentration-dependent increase in apoptotic bodies in AGS stomach cancer cells treated with piperine in (100 and 150 μM) (27), while Kim et al observed apoptotic bodies in HT-29 colon cancer cells treated with 40 μM piperine (28). These findings suggest that the decreases in the survival rates of A375SM and A375P treated with piperine were caused by apoptosis induction.…”
Section: Discussionmentioning
confidence: 98%
“…Piperine inhibits IL-1 β-induced p38 MAPK and STAT3 activation and, in turn, blocks the IL-1 β-induced IL-6 expression in TMK-1 gastric cancer cells [67]. It also decreases the protein levels of Bcl-2, Mcl-1, survivin, and increases the Fas levels, resulting in inhibition of the growth of HT-29, human colon cancer cells [68]. In HT-29 colon carcinoma cells, piperine reduces the levels of cyclins (D1 and D3), cyclin-dependent kinases (CDK-4 and 6), and upregulates p21/WAF1 and p27/KIP1 expression [69].…”
Section: Cancers Of the Gastrointestinal Tractmentioning
confidence: 99%
“…Inside the pepper containing piperine. As reported by Kim et al (2010) and Yaffe et al (2015), Piperine is effective to inhibit the growth of colon cancer cells in laboratory work [9,10]. To know how potential piperine able to be an alternative compound for colon cancer treatment, besides a laboratory experiment that had been conducted by Kim et al and Yaffe et al, the affinity of piperine toward responsible protein targeting for colon cancer is also necessary to be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The biological activity of piperine has been reported by many researchers, such as increases in the absorption of nutrients in the body, anti-inflammatory, analgesic, anticarcinogenic, antimutagenic, and antitumor [6][7][8]. Piperine also reported inhibiting the growth of colon cancer cells in laboratory work [9,10]. Ranged 35-77% of cases of colon cancer were found to be an excessive expression of epidermal growth factor receptor (EGFR) because of carcinogenic stimulation.…”
Section: Introductionmentioning
confidence: 99%